1999
DOI: 10.1103/physrevb.59.8745
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport and antiferromagnetism in the layered compoundBaCoS2

Abstract: BaCoS 2 is a Mott insulator with a Neél temperature (T N ) close to room temperature. In the ordered antiferromagnetic phase, the magnetic moments are confined in the Co 2 S 2 planes, and arranged in alternatingly directed ferromagnetic chains. We report on resistivity and thermopower measurements and on roomtemperature cell constants of samples of BaCoS z with nominal sulfur content 1.9рzр2.1. We discuss the effect of sulfur content on cell constants and band filling. The main observation is a crossover from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 25 publications
3
27
2
Order By: Relevance
“…12,15,25 The saddle point observed in the high resolution angle resolved photo emission experiments on the cuprate superconductors 10,48 point to a logarithmic density of states singularity ͑Van Hove singularity͒, close to the E f . Gasumyants et al 6 have attempted a quantitative estimation of the transport properties, under the narrow band considerations, using a few phenomenological parameters such as bandwidth (W D ), width of the conduction window (W ), and the degree of band filling (F).…”
Section: Narrow Band Modelmentioning
confidence: 94%
See 3 more Smart Citations
“…12,15,25 The saddle point observed in the high resolution angle resolved photo emission experiments on the cuprate superconductors 10,48 point to a logarithmic density of states singularity ͑Van Hove singularity͒, close to the E f . Gasumyants et al 6 have attempted a quantitative estimation of the transport properties, under the narrow band considerations, using a few phenomenological parameters such as bandwidth (W D ), width of the conduction window (W ), and the degree of band filling (F).…”
Section: Narrow Band Modelmentioning
confidence: 94%
“…33 Similar effects of hole depletion is observed in YBa 2 Cu 3 O 7Ϫ␦ samples with Pr doped at the Y site. 34 Fisher et al 25 have studied resistivity and thermopower of YBa 2 Cu 3Ϫx Co x O 7Ϫ␦ system and proposed the presence of a very narrow band near E f . Obertelli et al 9 have brought forth the close correlation existing between the thermoelectric power ͑TEP͒ and the superconductivity on several cuprate superconductors.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This compound was first synthesized by Chan et al [5], and it is isostructural with the Zintl compounds with the structure having 14 Yb 2 cations, an MnSb 9ÿ 4 tetrahedron, a Sb 7ÿ 3 unit, and 4 Sb 3ÿ anions. Initial studies on polycrystalline and single crystalline samples of this material indicated that the Mn magnetism is local in character with the exchange interaction between the well separated Mn 3 moments most likely due to conduction-electron mediated Rudermann-Kittel-Kasuya-Yoshida interactions [5,6]. The Curie temperature (T C ) is around 53 K, with robust ferromagnetic order setting in at low temperatures.…”
mentioning
confidence: 98%